Gender differences in sickness absence – the contribution of occupation and workplace - Laaksonen, Mikko; Mastekaasa, Arne; Martikainen, Pekka; Rahkonen, Ossi; Piha, Kustaa; Lahelma, Eero (Scandinavian Journal of Work, Environment & Health, 2010)
' ' OBJECTIVES ': 'The aim of this study was to examine whether differences in male and female occupations and workplaces explain gender differences in self-certified (1–3 days) and medically confirmed sickness absence episodes of various lengths (≥4 days, >2 weeks, >60 days). Analyses in the main ICD-10 diagnostic groups were conducted for absence episodes of >2 weeks. Furthermore, we examined whether the contribution of occupation is related to different distributions of female and male jobs across the social class hierarchy. ' ' METHODS ': 'All municipal employees of the City of Helsinki at the beginning of 2004 (N=36 395) were followed-up until the end of 2007. Conditional fixed-effects Poisson regression was used to control for differences between occupations and workplaces. ' ' RESULTS ': 'Controlling for occupation accounted for half of the female excess in self-certified and medically confirmed episodes lasting >60 days. In the intermediate categories, this explained about one third of the female excess. The effect of workplace was similar but weaker. Occupational and workplace differences explained the female excess in sickness absence due to mental and behavioral disorders, musculoskeletal diseases, and respiratory diseases. The effect of occupation was clearly stronger than that of social class in self-certified absence episodes, whereas in medically confirmed sickness absence episodes gender differences were to a large extent related to social class differences between occupations. ' ' CONCLUSIONS ': 'Differences between occupations held by women and men explain a substantial part of the female excess in sickness absence. Mental and behavioral disorders and musculoskeletal diseases substantially contribute to this explanation.
Keywords: fixed effect; gender; gender difference; man; men; occupation; occupational social class; sickness absence; social class; woman; women; working conditions; workplace